Sosialisasi Area Rawan Longsor Dan Upaya Mitigasinya di Kecamatan Gunungsari Kabupaten Lombok Barat - Arben Virgota; Baiq Farista; Supardiono; Rachmawati Noviana Rahayu; Astrini Widiyanti; Aida Muspiah; Nur Indah Julisaniah; Desak Made Devika Ratna Dewi; Nurul Hidayati; Baiq Annisya Salsabila (Universitas Mataram, 2024)
The Meninting Sub-watershed area is one of the areas prone to landslides. Most of the Meninting Watershed Area is included in the Gunungsar District Area. Two villages in Gunungsari District, namely Kekait Village and Bukit Tinggi Village, are included in the most widespread level of landslide vulnerability. The aim of this community service activity is to provide information and data regarding landslide-prone areas, increase the knowledge of the community regarding the risk of landslides, and mitigation actions that can be taken. The method used is the focus group discussion (FGD) method. The FGD was carried out in two stages, namely socialization material and discussion. The socialization was carried out to convey data and information regarding villages in Gunungsari District which are included in the Medium to High landslide prone category. The discussion was carried out to encourage the active participation of the Gunungsari community in designing landslide disaster mitigation efforts. The results of the service showed that there was a positive response from the people of Gunungsari District as indicated by an agreement on a follow-up plan to utilize the results of recommendations for landslide disaster mitigation and adaptation efforts. Mitigation efforts are carried out using physical and non-physical efforts. Physical efforts that can be carried out include spatial planning in the Meninting Watershed Area, application of bioengineering techniques using vetiver grass on cliff edges. Non-physical efforts that can be made are increasing understanding and knowledge about landslide disasters. Adaptation efforts are carried out by recognizing early signs of landslides, preparing disaster emergency equipment, and avoiding settlements in areas near rivers or steep slopes